Cuticular Characters Adapted to Volcanic Stress in a New Cretaceous Cycad Leaf from Patagonia, Argentina - Considerations on the Stratigraphy and Depositional History of the Baquero Formation - Archangelsky, Ana (1995)
Fil: Archangelsky, Ana. Museo Paleontológico E. Feruglio. Trelew. Chubut; Argentina